2018
DOI: 10.2196/10742
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficacy of an Educational Smartphone or Tablet App With Subdivided and Interactive Content to Increase Patients’ Medical Knowledge: Randomized Controlled Trial

Abstract: BackgroundModern health care focuses on shared decision making (SDM) because of its positive effects on patient satisfaction, therapy compliance, and outcomes. Patients’ knowledge about their illness and available treatment options, gained through medical education, is one of the key drivers for SDM. Current patient education relies heavily on medical consultation and is known to be ineffective.ObjectiveThis study aimed to determine whether providing patients with information in a subdivided, categorized, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 35 publications
3
67
1
Order By: Relevance
“…This could indicate a lack of engagement of participants or user-friendliness for the app itself. However, these rates are in line with studies on standalone eHealth applications assisting patients with OA in their preparation for the first consult with an orthopaedic surgeon, which could be used one or 2 weeks prior to consultation 48,49 . So, compared to other standalone eHealth interventions, our rates are comparable 50 .…”
Section: Table IIsupporting
confidence: 75%
“…This could indicate a lack of engagement of participants or user-friendliness for the app itself. However, these rates are in line with studies on standalone eHealth applications assisting patients with OA in their preparation for the first consult with an orthopaedic surgeon, which could be used one or 2 weeks prior to consultation 48,49 . So, compared to other standalone eHealth interventions, our rates are comparable 50 .…”
Section: Table IIsupporting
confidence: 75%
“…Recall may be impaired by pain, fatigue, sleep deprivation [55] and cognitive dysfunction associated with critical care [56]. ePROM platforms that systematically deliver individually-tailored patient information have been associated with increased information retention [57] and improved patient outcomes [54,58,59]. Patients reported that the capacity for the ePRO surgery system to monitor symptoms in real-time and provide individually tailored advice on demand enabled them to proactively and promptly manage their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a blended care intervention, involving interaction with a physiotherapist; therefore, it is not directly comparable with our study. One recently published RCT on the effectiveness of an educational smartphone and tablet app reported a 70% adherence rate [31]. Compared with other eHealth stand-alone interventions, these percentages are reasonably high [16,17].…”
Section: Discussionmentioning
confidence: 99%